Estudio de las habilidades de liderazgo y empresariales en un grupo de mujeres habitantes del sector rural del municipio de Siachoque (Boyacá) - Rodríguez Católico, Betty; Chaparro Lemus, Mariana (Universidad Antonio Nariño, 2023)
This research addresses the need to answer the problem question related to: What are the most significant leadership and business skills that women living in the rural sector of the municipality of Siachoque (Boyacá) have? Its main purpose is to determine these skills through three In the first phase, sociodemographic aspects were identified, in the second the categories of leadership and business skills were analyzed, and finally, the qualitative results were described.